1982
DOI: 10.1246/cl.1982.1605
|View full text |Cite
|
Sign up to set email alerts
|

A NEW MARINE CAROTENOID, MYTILOXANTHINONE FROM THE SEA SQUIRT, HALOCYNTHIA RORETZI

Abstract: A new marine carotenoid, mytiloxanthinone (3,8′-dihydroxy-7,8-didehydro-β,κ-carotene-3′,6′-dione) has been isolated from sea squirt, Halocynthia roretzi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Activated macrophages produce a large quantity of PGE 2 and NO, which causes a variety of inflammatory diseases, and the increased expression of COX-2 and iNOS are responsible for the production of PGE 2 and NO 11,12) . Therefore, the present results indicate that these carotenoids may exhibit anti-inflammatory effect through the down-regulation of the mRNA for COX-2 and iNOS as well as pro-inflammato- All-trans alloxanthin and all-trans diatoxanthin have been reported to be major carotenoids in H. roretzi 1,2) . Both carotenoids can be found in several algae such as the Cryptophyceae 27) and dinoflagellates 28) .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Activated macrophages produce a large quantity of PGE 2 and NO, which causes a variety of inflammatory diseases, and the increased expression of COX-2 and iNOS are responsible for the production of PGE 2 and NO 11,12) . Therefore, the present results indicate that these carotenoids may exhibit anti-inflammatory effect through the down-regulation of the mRNA for COX-2 and iNOS as well as pro-inflammato- All-trans alloxanthin and all-trans diatoxanthin have been reported to be major carotenoids in H. roretzi 1,2) . Both carotenoids can be found in several algae such as the Cryptophyceae 27) and dinoflagellates 28) .…”
Section: Discussionmentioning
confidence: 52%
“…Marine organisms are known to contain many kinds of carotenoids with unique structures. For example, the sea squirt Halocynthia roretzi contains a number of carotenoids including halocynthiaxanthin, alloxanthin, diatoxanthin, mytiloxanthin and fucoxanthinol with allenic, acetylenic and epoxicide structures in the molecule 1,2) . Previous studies have shown that holocynthiaxanthin exhibits an antiproliferative effect on various tumor cells 3) , inhibition of reverse transcriptases of immunodeficiency viruses 4) , and suppression of both superoxide and nitric oxide generation 5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These carotenoids were designated as amarouciaxanthin A and B, referring to Amaroucium from which the carotenoids were isolated. It is very interesting from a biosynthetic point of view that A. pliciferum possesses high contents of amarouciaxanthin A (3) and B (4) (See Results section).…”
mentioning
confidence: 99%
“…In addition to rodents, it has been reported that fucoxanthin is absorbed in other animals such as tunicates [37,38], chicken [39], and aquatic insects [40]. However, fucoxanthin was not absorbed in freshwater fish [40].…”
Section: Intestinal Absorption Of Xanthophyllsmentioning
confidence: 99%